2021
DOI: 10.1002/anie.202103888
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Enhanced Raman Spectroscopic Evidence of Key Intermediate Species and Role of NiFe Dual‐Catalytic Center in Water Oxidation

Abstract: NiFe-based electrocatalysts have attracted great interests due to the lowp rice and high activity in oxygen evolution reaction (OER). However,t he complex reaction mechanism of NiFe-catalyzedOER has not been fully explored yet. Detection of intermediate species can bridge the gap between OER performances and catalyst component/structure properties.H ere,w ep erformed label-free surface-enhanced Raman spectroscopic (SERS) monitoring of interfacial OER process on Ni 3 FeO x nanoparticles (NPs) in alkaline medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(121 citation statements)
references
References 62 publications
4
116
1
Order By: Relevance
“…Additionally, a more detailed analysis of the active sites of Ni 3 FeO x was performed by using label‐free surface‐enhanced Raman spectroscopy. [ 51 ] As illustrated in Figure 4e, Raman peaks between 1100 and 1200 cm −1 are attributed to the bridge and top‐mode OO − , respectively (Figure 4f). As potential rises up, the OO − Raman peak first appears and then disappears, meanwhile, Ni III ‐O peaks emerges, indicating that OO − is converted to O 2 with the help of Ni III sites.…”
Section: In Situ Optical Techniquesmentioning
confidence: 99%
“…Additionally, a more detailed analysis of the active sites of Ni 3 FeO x was performed by using label‐free surface‐enhanced Raman spectroscopy. [ 51 ] As illustrated in Figure 4e, Raman peaks between 1100 and 1200 cm −1 are attributed to the bridge and top‐mode OO − , respectively (Figure 4f). As potential rises up, the OO − Raman peak first appears and then disappears, meanwhile, Ni III ‐O peaks emerges, indicating that OO − is converted to O 2 with the help of Ni III sites.…”
Section: In Situ Optical Techniquesmentioning
confidence: 99%
“…Hu et al employed bifunctional Au@Ni 3 FeO x core−satellite superstructures to study the oxygen evolution reaction (OER) mechanism in alkaline medium. 101 O−O intermediate species locate at 1142 and 1170 cm −1 , indicating that Fe atoms could adsorb OH − and convert it to O 2− . The superoxide was further oxidized to O 2 through the electron transfer to Ni atoms (Figure 5d).…”
Section: Applied Studies Of the Solid−liquid Interface By In Situ Ram...mentioning
confidence: 99%
“…Water electrolysis technology is an important driving force for the green development of hydrogen energy industry. Hu et al employed bifunctional Au@Ni 3 FeO x core–satellite superstructures to study the oxygen evolution reaction (OER) mechanism in alkaline medium . O–O intermediate species locate at 1142 and 1170 cm –1 , indicating that Fe atoms could adsorb OH – and convert it to O 2– .…”
Section: Applied Studies Of the Solid–liquid Interface By In Situ Ram...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is an urgent need to develop efficient OER non-noble metal electrocatalysts. Researchers demonstrated that transition metal (TM) with empty d-electron orbital participates in the reaction as catalyst [8,9]. In particular, Ni-based transition metals are highly efficient OER catalysts [10,11].…”
Section: Introductionmentioning
confidence: 99%